Geographic distribution, clinical epidemiology and genetic diversity of the human oncogenic retrovirus HTLV-1 in Africa, the world’s largest endemic area - Gessain, Antoine; Ramassamy, Jill-Léa; Afonso, Philippe V.; Cassar, Olivier (Frontiers in Immunology, 2023)
The African continent is considered the largest high endemic area for the oncogenic retrovirus HTLV-1 with an estimated two to five million infected individuals. However, data on epidemiological aspects, in particular prevalence, risk factors and geographical distribution, are still very limited for many regions: on the one hand, few large-scale and representative studies have been performed and, on the other hand, many studies do not include confirmatory tests, resulting in indeterminate serological results, and a likely overestimation of HTLV-1 seroprevalence. For this review, we included the most robust studies published since 1984 on the prevalence of HTLV-1 and the two major diseases associated with this infection in people living in Africa and the Indian Ocean islands: adult T-cell leukemia (ATL) and tropical spastic paraparesis or HTLV-1-associated myelopathy (HAM/TSP). We also considered most of the book chapters and abstracts published at the 20 international conferences on HTLV and related viruses held since 1985, as well as the results of recent meta-analyses regarding the status of HTLV-1 in West and sub-Saharan Africa. Based on this bibliography, it appears that HTLV-1 distribution is very heterogeneous in Africa: The highest prevalences of HTLV-1 are reported in western, central and southern Africa, while eastern and northern Africa show lower prevalences. In highly endemic areas, the HTLV-1 prevalence in the adult population ranges from 0.3 to 3%, increases with age, and is highest among women. In rural areas of Gabon and the Democratic Republic of the Congo (DRC), HTLV-1 prevalence can reach up to 10-25% in elder women. HTLV-1-associated diseases in African patients have rarely been reported in situ on hospital wards, by local physicians. With the exception of the Republic of South Africa, DRC and Senegal, most reports on ATL and HAM/TSP in African patients have been published by European and American clinicians and involve immigrants or medical returnees to Europe (France and the UK) and the United States. There is clearly a huge underreporting of these diseases on the African continent. The genetic diversity of HTLV-1 is greatest in Africa, where six distinct genotypes (a, b, d, e, f, g) have been identified. The most frequent genotype in central Africa is genotype b. The other genotypes found in central Africa (d, e, f and g) are very rare. The vast majority of HTLV-1 strains from West and North Africa belong to genotype a, the so-called ‘Cosmopolitan’ genotype. These strains form five clades roughly reflecting the geographic origin of the infected individuals. We have recently shown that some of these clades are the result of recombination between a-WA and a-NA strains. Almost all sequences from southern Africa belong to Transcontinental a-genotype subgroup.